2016
DOI: 10.2140/jomms.2016.11.449
|View full text |Cite
|
Sign up to set email alerts
|

On the causality of the Rayleigh wave

Abstract: An explicit hyperbolic-elliptic formulation for surface Rayleigh waves is analysed with an emphasis on the causality of obtained results. As an example, a 3D moving load problem for a distributed vertical load is considered. A simple approximate solution is derived for a near-resonant regime, and the related point load solution is recast as a limiting case. It is shown that causality is characteristic only for the longitudinal wave potential along the surface, where it is governed by a hyperbolic equation mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…assuming absence of surface disturbances in front of a travelling load, we obtain, see Erbaş & Şahin (2016) for further detail,…”
Section: Sub-rayleigh Regimementioning
confidence: 99%
See 2 more Smart Citations
“…assuming absence of surface disturbances in front of a travelling load, we obtain, see Erbaş & Şahin (2016) for further detail,…”
Section: Sub-rayleigh Regimementioning
confidence: 99%
“…The interpretation of the formulae in this subsection, written in terms of |ξ| and |η|, relies on the implementation of the causality principle, see also Erbaş & Şahin (2016). In absence of a coating, when h = 0, the equation ( Similarly to the sub-Rayleigh case, we analyse the longitudinal and transverse cross-sections of the scaled horizontal displacement 7 Parabolic-elliptic model for a bending edge wave on a thin plate…”
Section: D Steady-state Problem For a Coated Half-spacementioning
confidence: 99%
See 1 more Smart Citation
“…We will therefore investigate the far-field asymptotic behaviour of the integrals as | | ≫ 1 and * ∼ 1. It may be shown that while the first integral in (17) does not have any stationary points in the integration interval, i.e., any points for which the derivative vanishes, the second integral has one, which is obtained by taking the derivative of the exponent with respect to , given by * = 2(1 − 3 * 2 + √1 + 3 * 2 ) 9 *…”
Section: The Super-rayleigh Regimementioning
confidence: 99%
“…It is clearly seen in these graphs that the greater values of the parameter reduces the magnitude of the displacement resulting in a more uniform distributed profile, which is an expected result (cf. [17,18]). It should be noted that the values of the parameter either corresponds to the amplitude of the profile of the load for fixed values of the material parameter and the coating thickness ℎ; or, to the coating thickness ℎ for fixed values of , and .…”
mentioning
confidence: 99%